Large-mesopore hierarchical tungsten trioxide hydrate with exposed high energy facets: Facile synthesis and enhanced photocatalysis. (October 2016) - Gu, Yiran; Zhuo, Qian; Wu, Dongfang
Abstract: Developing highly active photocatalysts for water treatment is of vital importance. A large-mesopore hierarchical WO3 hydrate photocatalyst with exposed high energy facets was synthesized via a facile hydrothermal method using sodium chloride as structure-directing agent. The forming model of the hierarchical structure was discussed, and photogenerated oxide species were investigated. It is shown that the orthorhombic WO3 ·1/3H2 O photocatalyst is of a hierarchical structure assembled by various 2-dimension nanosheets and that its average pore diameter reaches approximately 33.2 nm. Besides, it could decompose 92% of rhodamine B (Rh B) under visible light irradiation within four hours. The enhanced photocatalytic efficiency is attributed to the exposed high energy (002) crystal facets of hierarchical structure, and to the large mesopores existing between crossed nanosheets which help to charge carriers separation, adsorption of reactants and desorption of product molecules. Furthermore, the catalyst displays an excellent photocatalytic stability, indicating its broad application in water pollution treatment.